(untitled) (Південний архів (історичні науки), 2023)
Purpose. The purpose of the article is a comparative analysis of the personalities of Maria (Marusi) Nikiforova and Galina (Agafia) Kuzmenko. These women were influential personalities in the Ukrainian anarchist movement in 1917–1919. Fate, each in its own way, connected them with Nestor Ivanovich Makhno – an original and colorful personality of the Ukrainian revolution, the founder and commander of the Insurgent-Partisan Ukrainian Army by N. Makhno. Our research will be a part of gender studies of Ukrainian historiography, due to insufficient attention to this dimension among researchers of the period of liberation struggles. Also, the task of the article is to draw attention to little-known or insufficiently developed sources: mnemonic, oral, visual, which relate to gender studies of the revolutionary period 1917–1921. Another task is to refute myths and fakes related to these women, especially when it comes about Marusya Nikiforova. Methods. The stated purpose of the article led to the selection of methodical optics applied to the analysis of the issues of the publication. The main thing is the gender approach, through the prism of which the actions of these individuals and the motives of the decisions they made will be considered, which is often overlooked by researchers. The territorial research method will also be applied. Special attention will be paid to the part of Central Ukraine in the period 1918–1919. It is this micro-region of the Right Bank, whose borders are crossed by the Sinyukha River in the west, Dnipro – in the East, Ros – in the North, Southern Bug – in the South – played an important role in the lives of these women in the above-mentioned period. Another important research method is comparative studies. We will use it to compare the life path of these personalities in the studied period. The oral history method will be used to analyze the sources; during the analysis of Halyna Kuzmenko’s diary, methods of source deconstruction and historical hermeneutics. An interdisciplinary toolkit will be used to analyze literary sources. Results. Sources were analyzed: written, oral, visual, literary, relating to the personalities of M. Nikiforova and H. Kuzmenko and their role in the history of the Ukrainian anarchist movement under the conditions of the revolutionary period of 1917–1921. With the help of the comparative method, the features of the worldview, activity, and motivation of approval were examined decisions made by these individuals and their impact on the personality of Nestor Makhno. Inaccurate information related to these individuals has been refuted. The place and significance of these individuals in the history of the Ukrainian anarchist movement during the liberation struggle of 1917–1921 has been clarified. Conclusions. Gender studies remain an interesting intellectual platform of Ukrainian historiography. And the revolutionary era of 1917–1921 still has many bright female personalities who can become an object and subject of research for professional historians, which will contribute to an objective view of the role of women in the history of the revolutionary period. We hope that our research will contribute to the renewal of interest in gender issues in Ukrainian historiography.